Reflections by nursing managers and ingerences of their work in Primary Health Care in a municipality of the metropolitan region of Belém (Research, Society and Development, 2021)
Management is a fundamental step in the implementation of health policies, as it has the capacity to mediate the relations of needs demanded by users of the health system. As a manager, the nurse acts as an important professional in the implementation of the health system and services in the country. The present study aimed to analyze how nurses who manage a medium-sized municipality perceive their influence on Health Policies. This is an exploratory research with a qualitative approach. Data collection took place through a semi-structured interview script. In data processing, we used the software IRAMUTEQ, for their analysis, the Descending Hierarchical Classification techniques were used. Among the 16 Basic Health Units (UBS) included, only 01 unit did not have a nurse as a manager. In the other 15 units, 04 nurse managers refused to participate in the interview and 03 nurses were on leave. The interview was conducted with 08 nurse managers. There was a low demand for postgraduate studies in the area of health management for occupying positions, little time for professional training and acting as a manager. It was noted that all respondents have temporary contracts at the UBS. Thus, the high turnover of managers in the job is presumed. It is concluded that the profile of nurse managers in the municipality is configured for a short time of training and little time in management.